Nutrition, the digestive system and immunity in COVID-19 infection - Bold, Justine; Harris, Miranda; Fellows, Lindsey; Chouchane, Manal (Gastroenterology and hepatology from bed to bench, 2020)
The current review aimed to synthesize the literature on the complex relationship between food consumption and nutritional status as well as the digestive system in order to examine the relationship between immunity and potential responses to COVID-19 infection. The goal is to help inform the many healthcare professionals working with COVID-19 patients. A literature search was performed on PubMed, Scopus, and EMBASE databases. Hand searches were also undertaken using Google and reference lists to identify recent evidence. Studies were critically appraised, and the findings were analyzed by narrative synthesis. Nutritional status can impact immunity in several ways, including affecting susceptibility to infection, severity of disease, and recovery time, and is therefore a significant consideration in the management of COVID-19. COVID-19 can also impact digestive function, which can further impact nutritional status. The role of Vitamin D deficiency in vulnerability to severe respiratory infections, including COVID-19, has been recognized, and it may have a role in treatment where deficiency is indicated. Healthcare professionals should be aware that obesity may be accompanied by micronutrient malnutrition including vitamin D deficiency and alterations in the microbiome and inflammatory responses, which can further impact immunity and disease severity. Multidisciplinary team-work is recommended in the management of patients with COVID-19, and approaches should include a consideration of nutritional status (both macronutrients and micronutrients), body weight, and gastrointestinal signs and symptom.